2015
DOI: 10.5152/tjar.2014.45220
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dexmedetomidine Versus Ketamine-Propofol Combination for Sedation in Cataract Surgery

Abstract: Objective: The aim of this study is to compare the sedative properties and haemodynamic and respiratory effects of dexmedetomidine and a ketamine-propofol combination (ketofol), which are expected to have minimal effects on spontaneous breathing. Methods:Sixty patients were enrolled in this prospective randomised study. Patients were divided into 2 groups according to the administration of dexmedetomidine (Group D) and ketofol (Group K). Target sedation level was determined as a Ramsay Sedation Score of 3. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 32 publications
(35 reference statements)
1
28
0
Order By: Relevance
“…Seven studies in our review demonstrated significant reductions in IOP [13,15,[18][19][20][21]23]. One study reported a 3.8 mmHg decrease in IOP compared to control after a 1 mcg/kg bolus of dexmedetomidine [21].…”
Section: Intraocular Pressurementioning
confidence: 83%
See 4 more Smart Citations
“…Seven studies in our review demonstrated significant reductions in IOP [13,15,[18][19][20][21]23]. One study reported a 3.8 mmHg decrease in IOP compared to control after a 1 mcg/kg bolus of dexmedetomidine [21].…”
Section: Intraocular Pressurementioning
confidence: 83%
“…One study noted that dexmedetomidine-treated patients required more time to achieve an Aldrete score of 10 when compared to midazolam-treated patients [median interquartile range (IQR): 45 (36-54) vs 21 (10-32) min, P < 0.01] [12]. Prolonged PACU discharge times were also noted in a study comparing dexmedetomidine to ketofol [mean time to achieve Aldrete score 9 (standard deviation (SD)): 24.9 (4.5) vs 16.1 (2.1) min, P < 0.001] [18]. These findings were not consistent with one study that utilized intravenous dexmedetomidine 1 mcg/kg followed by patient-controlled sedation with dexmedetomidine, which demonstrated no statistically significant differences in Aldrete scores at 30 min postoperatively compared to patients who received no sedation [21].…”
Section: Pacu Discharge and Recovery Timesmentioning
confidence: 98%
See 3 more Smart Citations